Mechanical Properties of Experimental Composites with Different Photoinitiator - de Resende, Luis Felipe Marques; Catelan, Anderson; Baroudi, Kusai; Palialol, Alan Rodrigo Muniz; de Resende, Alexandre Marques; Andreucci, Ana Carolina; Zanatta, Rayssa Ferreira; Liporoni, Priscila Christiane Suzy (European Journal of Dentistry, 2021)
Objective The effect of different photoinitiators on mechanical properties of experimental composites was evaluated.Materials and Methods Resin composites were formulated by using a blend of bisphenol A-glycidyl and triethylene glycol (50/50 wt%) dimethacrylate monomers, and 65 wt% of barium aluminium silicate and silica filler particles. Photoinitiators used were 0.2% camphorquinone (CQ) and 0.8% co-initiator (DMAEMA); 0.2% phenyl-propanedione and 0.8% DMAEMA; 0.1% CQ + 0.1% phenyl propanedione and 0.8% DMAEMA; 0.42% mono(acyl)phosphine oxide (MAPO); and 0.5% bis(acyl)phosphine oxide (BAPO). Specimens (n = 10) were light cured by using a multiple-emission peak light-emitting diode for 20 seconds at 1,200 mW/cm2 of irradiance and Knoop hardness and plasticization, depth of cure, flexural strength, and elastic modulus were evaluated. Data were statiscally analyzed at significance level of α = 5%.Results Experimental composites containing MAPO and BAPO photoinitiators showed the highest values of flexural strength, elastic modulus, top surface hardness, and lower hardness reduction caused by alcohol compared with CQ. Composites containing CQ and PPD showed similar results, except for depth of cure and hardness of bottom surface.Conclusion BAPO and MAPO showed higher flexural strength, elastic modulus, hardness on top surface, and lower polymer plasticization to CQ.
Keywords: resin composites; hardness; elastic modulus; photoinitiators